PROYEKSI KEBUTUHAN AIR BAKU KOTA TASIKMALAYA PADA TAHUN 2025 - Nugraha Sadeli Utama (Jurnal Infrastruktur, 2017)
Water is a basic requirement that is needed by living things. Water is also need in every household, agricultural, economic, and industrial. A common problem that we faced today is the consumption of water continues to increase in line with population growth, while diminishing water resources in terms of quality and quantity. To calculate the water needs, a study be required on population projections and projected water requirements in the future. In this study, the calculation of the water demand consist of calculation of domestic water needs (household), calculation of non-domestic water needs (municipal), and calculation of industrial water needs. The projection method used in this study is Mathematical Logistic Curve Method. Based on calculations that have been done, population of Tasikmalaya in 2025 are 668,281 peoples, water demand of Tasikmalaya in 2025 is 2,100 liters/sec, and the water avaibility of Tasikmalaya in 2025 is 944.18 liters/sec. Avaibility less than requirement, so there is a water deficit 1,155.82 liters/sec.